Phenolic Response to Walnut Anthracnose (Ophiognomonia leptostyla) Infection in Different Parts of Juglans regia Husks, Using HPLC-MS/MS - Aljaz Medic; Anita Solar; Metka Hudina; Robert Veberic (Agriculture, 2021)
This study compares the individual phenolic response of husk tissues of Juglans regia L., infected to different degrees of severity with walnut anthracnose, which is one of the most serious and widespread walnut diseases worldwide. A comparison among three differently susceptible cultivars, ‘Franquette’, ‘Milotai 10’ (‘M10’), and ‘Milotai intenziv’ (‘M10-37’), is made. In our methodology, high performance liquid chromatography coupled with mass spectrometry is used to identify and quantify the compounds. Our results show that flavanols, flavonols, and naphthoquinones account for more than 95% of the phenolic compounds identified in the walnut husk. The higher total analyzed phenolic content in tissues is more affected by walnut anthracnose confirmed that phenolics play a major role in the plant’s response against pathogens. A difference between cultivars is observed, since French cultivar ‘Franquette’ responds differently to walnut anthracnose infection than Hungarian cultivars ‘M10’ and ‘M10-37’. Naphthoquinones and flavanols have a very similar response to walnut anthracnose infection. The resistance of cultivars may be due to the reaction time of the plant and the speed with which it recognizes the pathogen and responds quickly to the infection by containing it while it has not yet spread. Flavonols may be the most important phenolic compounds in disease control, since they respond more rapidly to infection than flavanols and naphthoquinones. They also play an inhibitory role in the early stages of viral and bacterial infections.